REPRESENTASI DEMONSTRASI DI INDONESIA DALAM MEDIA INTERNASIONAL BERBAHASA ARAB - Husodo, Irfandi Fiqra (Multikultura, 2026)
The demonstrations that took place in Indonesia from late August 2025 to early September 2025 attracted global attention and were reported by Arabic-language international media. News media can produce meaning and shape international public perception in their representation of demonstrations in Indonesia. This study aims to analyze the representation of the demonstrations in Indonesia in Arabic-language international media, namely Al-Jazeera Mubasher, Al-Araby Al-Jadid, Al-Arabiya, and BBC Arabic. This study uses a qualitative approach with Norman Fairclough's Critical Discourse Analysis method combined with van Dijk's ideological square. The research data consists of four news articles selected based on the focus of the issue in the news headline, namely demonstrators, the government, victims, and the general situation. The results of the study show significant differences between the four media outlets in their representation of demonstrations in Indonesia, in line with their ideologies and interests in the global public sphere. Al-Arabiya and Al-Araby Al-Jadid tend to represent demonstrations as a threat to stability and the economy. BBC Arabic and Al-Jazeera Mubasher place greater emphasis on social justice, human rights, and the legitimacy of the people's demands.